The Role of Women in Family Resilience During the Covid-19 Pandemic - Atma Ras; Ridwan Syam; Nuvida Raf; Musrayani Usman; St. Radiah (International Journal of Qualitative Research, 2022)
This study aims to describe and analyze the important role that women can play in the resilience of education and the family economy to deal with situations and conditions affected by Covid-19. The research was conducted using a qualitative approach, because this study used a qualitative approach, in collecting data, observations, interviews, and documentation studies were carried out. The data analysis process that the researcher uses consists of three stages, namely data reduction, data presentation, and concluding. The results of the study show that the important role that women can play in the resilience of family education in the face of the Covid-19 pandemic is assisting children in learning, supervising children's learning processes, facilitating children in learning, and advising and encouraging children when they are bored with learning. In addition to maintaining family education, women also play an important role in maintaining the family economy by earning additional income in the family economy and being good financial managers in the household.